EcoRII can be activated to cleave refractory DNA recognition sites. - Krüger, D H (1988)
EcoRII restriction sites [5'-CC(A/T)GG] in phage T3 and T7 DNA are refractory to cleavage by EcoRII, but become sensitive to cleavage in the presence of DNAs which contain an abundance of EcoRII sensitive sites (e.g. pBR322 or lambda DNA). Studies using fragments of pBR322 containing different numbers of EcoRII sites show that the susceptibility to EcoRII cleavage is proportional to the number of sites in the individual fragment. We postulate that EcoRII is the prototype of restriction endonucleases which require at least 2 simultaneously bound substrate sites for their activation. EcoRII sites are refractory when they occur at relatively low frequency in the DNA. The restriction enzyme can be activated by DNA with a higher frequency of sites.